Apolipoprotein B gene variants are involved in the determination of blood glucose and lipid levels in patients with non-insulin dependent diabetes mellitus - Duman Süsleyici, Belgin; Öztürk, Melek; Yılmazer, Selma; Çağatay, Penbe; Hatemi, Hüsrev (My University, 2006)
We have examined the frequency of the EcoRI, XbaI and MspI RFLPs of the apolipoprotein B (apo B) gene in 110 type 2 diabetic patients and 91 healthy control subjects in order to ascertain whether variation in this gene may influence the development of non-insulin dependent diabetes mellitus (type 2 diabetes). Serum lipids including total-cholesterol (T-Chol), triacylglycerol (TAG), apolipoprotein E (apo E), apolipoprotein AI (apo AI), apolipoprotein B and lipoprotein (a) (Lp(a)) were analysed. Genomic DNA was extracted and the apo B polymorphic regions amplified by the polymerase chain reaction. Regions carrying EcoRI, XbaI, and MspI restriction sites present in the apo B gene were amplified and digested separately by the respective enzymes. No significant difference for genotypic frequencies was observed for the EcoRI, XbaI and MspI restriction sites in type 2 diabetic patients as compared to controls. Type 2 diabetic patients and controls with EcoRI þ/þ and XbaI þ/þ genotypes had higher apo E levels. The MspI þ/þ genotype is more frequent in the patient and control groups with elevated T-Chol. Furthermore, the EcoRI / , XbaI / , and MspI þ/þ genotypes were found to be significantly more frequent in type 2 diabetic patients with higher blood glucose levels. This study identifies the apo B gene polymorphisms in modulating plasma lipid/lipoprotein and glucose levels in patients with type 2 diabetes.
Keywords: non-insulin dependent diabetes mellitus; apolipoprotein B; polymorphism